Hypertension prevalence and associated risk factors among bank employees working in an urban area of Marathwada region, Maharashtra, India - Shekhar, Saket; Holambe, Vimal M. M.; Bansode, Jagdish D.; Edake, Sachin S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Epidemiologic transition of diseases is occurring in recent times throughout the world. The morbidity, disability and mortality burden is now more because of non-communicable diseases. Cardiovascular diseases are number one killer throughout the world. Hypertension has been found to be an independent and consistent risk factor for cardiovascular diseases. Bank employee’s job being sedentary in nature and involving cash management related stress makes bank employees a potential occupational group to develop hypertension. So, this study was planned to assess the prevalence of hypertension in bank employees in the urban area of Latur district, Maharashtra. Methods: A cross-sectional observational study was carried out between January 2016 to December 2016 among all the bank employees working in urban area of Latur, Maharashtra. Approval from institutional ethics committee was obtained beforehand. Results: Total 577 bank employees were surveyed for this study. 32.4% of subjects were found to be hypertensive. Association of higher age group and managerial cadre of employment were found to be statistically significant. Conclusions: Bank employees have a higher prevalence of hypertension as compared to general population. Bank employees are an occupational risk group to develop hypertension.